Real Insights into Virtual Minds: A Comparison of Private and Public School Teachers’ Perceptions of ChatGPT - Mustafa Taktak (Journal of Learning and Teaching in Digital Age, 2026)
The rapid advancement of artificial intelligence in education necessitates a systematic examination of teachers’ perceptions and attitudes toward these emerging technologies. This study aims to comparatively analyze the perceptions of teachers working in public and private schools in Turkey regarding the use of ChatGPT. The research was conducted with a sample of 240 teachers, comprising 124 from public schools and 116 from private schools. The findings reveal significant differences in teachers’ perceptions based on school type, frequency of ChatGPT use, and professional seniority. Notably, among private school teachers, increased professional experience correlates with more positive attitudes toward ChatGPT, whereas no comparable effect of seniority was observed among public school teachers. This divergence underscores the influence of institutional culture and organizational context on technology adoption processes. The results highlight that teachers’ institutional affiliation and professional tenure are critical determinants shaping their acceptance and perception of AI-driven educational tools. This study offers valuable insights for policymakers and educational leaders in designing targeted professional development and policy frameworks that support the effective and sustainable integration of artificial intelligence technologies in diverse school environments.